X-ray crystal structure analysis of N'-acetyl-N'-phenyl-2-naphthohydrazide - Sharma, Varun; Karmakar, Indrajit; Brahmachari, Goutam; Gupta, Vivek Kumar (European Journal of Chemistry, 2022)
N'-Acetyl-N'-phenyl-2-naphthohydrazide, a biologically relevant organic molecule, was synthesized following a reported method and characterized based on its single X-ray crystallographic studies. The present manuscript deals with its detailed molecular interactions and X-ray crystal structure. Its space group is P-1 with the following unit cell parameters: a = 8.9164(7), b = 9.7058(9), c = 17.7384(12) Å, α = 88.308(7)°, β = 89.744(6)°, γ = 86.744(7)° and Z = 2. Crystal structure was solved by direct method and refined by full matrix least squares procedure to a final R value of 0.0580 and to a GOOF value of 1.066. The X-ray diffraction analyses showed that the asymmetric unit contains two crystallographically independent molecules. The crystal structure is stabilized by elaborate network of N-H···O and C-H···O hydrogen bonds along with C-H···π and π···π interactions to form supramolecular structures.